Desenvolvimento sustentável e arranjos produtivos locais : o caso da cerâmica artesanal do município de Santana do São Francisco - SE - Matos, Silvia Maria Santos (2004)
The lack of development strategy reaches most of the cities in Brazil. In the perspective of sustainable development the support to productive systems and arrangements contemplate at the same time economic, social, cultural and environmental aspects. The present study has as the principal objective to analyse the dynamic in the ceramic workmanship productive arrangements on Santana do São Francisco municipal district to identify its principal actors and to analyse the processes of learning and the degree of involvement of the ones who work on that activity, the structure and the organization of the production system, as well as the utilization of natural resources, and the analyses of the local governorship and of the public and institutional policies that support the activity. The data were collected from primary sources by means of personal interviews with all the people that compose the work force in the arrangements artisans, people who prepare and transport the clay, firewood suppliers, and also the local coordination institutions and fomentation representatives who give support to the activity. It can be observed that the activity is characterized mostly by domestic labour that gains an average income that ranges from one to two minimum salaries. By and large the learning of the technique happens inside the family environment and/or in the work place. The organization of the production is distributed within 80 productive units. Most of it has a precarious physical infra-structure which makes it difficult the execution of the services and the presentation of the product. In the arrangement, the control of the productive processes shows many deficiencies, among them the supplying of imputs. The clay, the principal raw material, is being donated, leaving the artisans in a situation of dependency. The type of piece that is produced is determined in most of the cases by the buyers of the product. The pieces are sold principally to brokers and to the shopping owner from Aracaju, Bahia and Alagoas states. The sales have been going down in the arrangements in the last five years, although the perspective is that it may be increased for most of the artisans. The trajectory of development of the arrangements points to the difficulty of integration among their members. It happens on account of the problems that took place in local government institutions previous administrations that brought a sense of distrust and disillusion among the artisans and provoked in the arrangements a disloyal competition among them. Another difficulty is the absence of control in the production cost whose price making happens in an aleatory way. The propositions of policies indicate that it s necessary the establishment of an integrated and specific strategy that coordinates all the necessary actions to the development of the productive arrangements of ceramics on Santana do São Francisco.